Beneficial effects montelukast, cysteinyl-leukotriene receptor antagonist, on renal damage after unilateral ureteral obstruction in rats - Ötünçtemur, Alper; Özbek, Emin; Çakır, Süleyman Sami; Dursun, Murat; Çekmen, Mustafa Baki; Polat, Emre Can; Özcan, Levent; Somay, Adnan; Özel Özbay, Nurver (Brazilian Society of Urology, 2015)
Introduction: Ureteral obstruction is a common pathology and caused kidney fibrosis and dysfunction at late period. In this present, we investigated the antifibrotic and antiinflammatory effects of montelukast which is cysteinyl leukotriene receptor antagonist, on kidney damage after unilateral ureteral obstruction(UUO) in rats. Materials and Methods: 32 rats divided four groups. Group 1 was control, group 2 was sham, group 3 was rats with UUO and group 4 was rats with UUO which were given montelukast sodium (oral 10 mg/kg/day). After 14 days, rats were killed and their kidneys were taken and blood analysis was performed. Tubular necrosis, mononuclear cell infiltration and interstitial fibrosis scoring were determined histopathologically in a part of kidneys; nitric oxide(NO), malondialdehyde(MDA) and reduced glutathione(GSH) levels were determined in the other part of kidneys. Urea-creatinine levels were investigated at blood analysis. Statistical analyses were made by the Chi-square test and one-way analysis of variance (ANOVA). Results: There was no difference significantly for urea-creatinine levels between groups. Pathologically, there was serious tubular necrosis and fibrosis in group 3 and there was significantly decreasing for tubular necrosis and fibrosis in group 4(p<0.005). Also, there was significantly increasing for NO and MDA levels; decreasing for GSH levels in group 3 compared the other groups(p<0.005). Conclusion: We can say that montelukast prevent kidney damage with antioxidant effect, independently of NO.
WOS: 000354634500014
PubMed ID: 26005969
Keywords: Montelukast [Supplementary Concept]; Cysteinyl-Leukotriene [Supplementary Concept]; Renal Insufficiency; Ureteral Obstruction